## Essential University Physics: Volume 1 (4th Edition)

$(a)\space15.64\space m/s$ $(b)\space51.3\space ft/s$
(a) We know 1 mi = 1609 m and 1 h = 3600s First of all, let's convert 35 mi/h into m/h as follows. $35\space mi/h\space = (\frac{35\space mi}{h})\times(\frac{h}{3600\space s})$ $\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space=\space 56315\space m/h$ After that let's convert h into s as follows. $35\space mi/h\space =\space 56315\space m/h$ $\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space =\space (\frac{56315\space m}{h})\times(\frac{h}{3600\space s})$ $\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space =\space 15.64\space m/s$ (b) we know 1 m = 3.28 ft Now we can multiply the result in (a) by 3.28 ft/m to get the answer $35\space mi/h\space =\space 15.64\space m/s\space =\space 15.64\space m/s\space \times\space 3.28\space ft/m$ $\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space\space =\space 51.3\space ft/s$